Pedagogical Approach for Effective Teaching in Learning Space - R. Bhuvanya, T. Kujani, P. Matheswaran (International Journal of Advanced Science and Technology, 2020)
Education which has been derived from the Latin word ‘educationem’ where teaching and learning is essential. In general, the traditional method of teaching is referredas a teacher centered approach which was believed to be a tool for knowledge gaining. Here teacher will act as a controller in the class room and the students will remain passively in the atmosphere. Class room teaching was believed to be a thought provoking environment but the student’s participation in the environment is a major missing. So, it resulted in a lack of learning and active participation in various activities and the interaction between the students and teachers became very less. Though this method of teaching has been used for long days, It is considered to be ineffective process as it is not able to invoke the student’s interest and involvement in the class. The drawback to be mentioned is, there is a probability that some teachers misinterpret this teaching method and they could utilize it for their own advantage. In order to overcome all the proposed issues, it’s a right time to approach to Active Learning Methodologies. Hence here we justified the usage of adapting Active Learning Methodologies which will make our environment as a provoking one.